CONCEPTOSPHERE AS AN ELEMENT OF CULTURAL-PHILOSOPHY MODEL OF A LITERARY AND ARTISTIC WORK - Ivan Yu. Makarchuk (Russian Studies in Culture and Society)
The humanities are in a relentless search for optimal and more effective (compared to existing) research methods and strategies. The author of this article, as a research method, develops the general theoretical foundations of the cultural-philosophical model of a literary and artistic work, which can be used in the study of the creative heritage of various writers. The structural elements of the cultural-philosophical model of a literary and artistic work, along with the concept sphere of the corresponding literary and artistic work, include: the sum of humanitarian studies of a literary and artistic work, its main cultural and philosophical idea, genre, as well as a writer’s biography. Description of the concept sphere as an element of the cultural-philosophical model of a literary and artistic work is the purpose of this article.